On the twist-bend nematic phase formed directly from the isotropic phase. Issue 1 (2nd January 2016) - Dawood, Alya A.; Grossel, Martin C.; Luckhurst, Geoffrey R.; Richardson, Robert M.; Timimi, Bakir A.; Wells, Neil J.; Yousif, Yousif Z.
Abstract: The intriguing twist-bend nematic (NTB ) phase is formed, primarily, by liquid crystal dimers having odd spacers. Typically, the phase is preceded by a nematic (N) phase via a weak first-order transition. Our aim is to obtain dimers where the NTB phase is formed directly from the isotropic (I) phase via a strong first-order phase transition. The analogy between such behaviour and that of the smectic A (SmA)–N–I sequence suggests that this new dimer will require a short spacer. This expectation is consistent with the prediction of a molecular field theory, since the decrease in the spacer length results in an increase in the molecular curvature. A vector of odd dimers based on benzoyloxybenzylidene mesogenic groups with terminal ethoxy groups has been synthesised with spacers composed of odd numbers of methylene groups. Spacers having 5, 7, 9 and 11 methylene groups are found to possess the conventional phase sequence NTB –N–I; surprisingly, for the propane spacer, the NTB phase is formed directly from the I phase. The properties of these dimers have been studied with care to ensure that the identification of the NTB phase is reliable. Graphical Abstract: